Logging residues conserve small mammalian diversity in a Malaysian production forest. (February 2016) - Yamada, Toshihiro; Yoshida, Satoru; Hosaka, Tetsuro; Okuda, Toshinori
Abstract: The extraction of large trees by selective logging in tropical production forests often results in a reduction of natural fallen trees for a long period after logging has been completed. This causes a population decrease for various small mammals that exploit fallen trees to live. We expect that logging residues, which are unmerchantable upper parts of logged trees, will alleviate the negative effects of the reduced volume of naturally fallen trees immediately after logging. To examine this issue, we compared the activity of small mammals in forest floor habitats with and without logging residues in a Malaysian production forest using a camera trapping technique. We tested the hypothesis that the activity of small mammals would be higher on forest floors with logging residues when compared with those without them; our study affirmatively supported this hypothesis. Therefore, logging residues are expected to have positive roles in maintaining small mammal diversity at the ground level in production forests. Recently commercial use of logging residues has been promoted; however, removing all logging residues from a production forest would severely and negatively affect the diversity of ground-dwelling small mammals. In addition, for small mammals which essentially require fallen trees to survive, populations will shrink or in a worst case scenario, they would become extirpated from production forests if all logging debris is removed. Highlights: This study examined how logging residues may help maintain small mammal diversity. Small mammal diversity was higher in forest floor areas with logging residues. Retaining residues will help mitigate the negative effects of logging operations.